General Recommendations for Fertilization of Turfgrasses on Florida Soils - Jerry B. Sartain (EDIS, 2015)
In many neighborhoods, people envy the individual with the most beautiful lawn and think they cannot grow a lawn of equal quality. That is not necessarily true. A well-maintained lawn only requires some knowledge about fertilization, watering, pest control, and mowing. This publication provides basic information about fertilization. By far, the best approach to a proper fertilization program is to start with a soil test, but, if a soil test is not available, these guidelines can be used for a general turfgrass fertilization program. Original publication date May 1991. Revised August 2013 and August 2015.